Immunoexpression pattern of autophagy mediators in alveolar bone osteoclasts following estrogen withdrawal in female rats - Florencio-Silva, Rinaldo; Sasso, Gisela Rodrigues da Silva; Sasso-Cerri, Estela [UNESP]; Simões, Manuel de Jesus; Cerri, Paulo Sérgio [UNESP] (Springer Nature, 2021)
It is known that estrogen deficiency increases osteoclast formation and activity. Autophagy, a cell survival pathway, has been shown to be crucial for osteoclast function. However, little is known about the effects of estrogen depletion on osteoclast autophagy. Here, we evaluated the effects of estrogen deficiency in the immunoexpression of autophagy mediators in alveolar bone osteoclasts of ovariectomized rats. Twelve adult female rats were ovariectomized (OVX-group) or SHAM-operated (SHAM-group). After three weeks, the rats were euthanized and maxillary fragments containing alveolar bone of the first molars were processed for light microscopy or transmission electron microscopy (TEM). Paraffin-sections were subjected to the TRAP method (osteoclast marker) or to the immunohistochemical detections of beclin-1, LC3α, and p62 (autophagy mediators); araldite-sections were processed for TEM. The number of TRAP-positive osteoclasts and the number of immunolabeled-multinucleated cells (MNCs) along the alveolar bone surface of the first molar were computed. The number of TRAP-positive osteoclasts and the number of beclin-1-, LC3α- and p62-immunolabelled osteoclasts were significantly higher in OVX-group than the SHAM-group. MNCs were frequently located juxtaposed to Howship lacunae along the alveolar bone surface, indicating that these cells are osteoclasts. TEM revealed osteoclasts exhibiting autophagosomes. Our data indicate that autophagy plays an important role during estrogen deficiency-induced osteoclastogenesis. Thus, our results contribute to a better understanding on the role of autophagy on osteoclasts under estrogenic deficiency, and reinforce the idea that modulation of autophagy may be a useful tool to inhibit excessive oral bone resorption in post-menopausal women.
Keywords: Alveolar bone; Autophagy; Estrogen withdrawal; Osteoclast; Rat